The role of primed and non-primed MSC-derived conditioned media in neuroregeneration - Hudakova, Nikola; Mudronova, Dagmar; Marcincakova, Dana; Slovinska, Lucia; Majerova, Petra; Maloveska, Marcela; Petrouskova, Patricia; Humenik, Filip; Cizkova, Dasa (Frontiers in Molecular Neuroscience, 2023)
Introduction With growing significance in nervous system repair, mesenchymal stem cell-derived conditioned media (MSCCM) have been used in cell-free therapies in regenerative medicine. However, the immunomodulatory and neuroregenerative effects of MSCCM and the influence of priming on these effects are still poorly understood. Methods In this study, by various methods focused on cell viability, proliferation, neuron-like differentiation, neurite outgrowth, cell migration and regrowth, we demonstrated that MSCCM derived from adipose tissue (AT-MSCCM) and amniotic membrane (AM-MSCCM) had different effects on SH-SY5Y cells. Results and discussion AT-MSCCM was found to have a higher proliferative capacity and the ability to impact neurite outgrowth during differentiation, while AM-MSCCM showed more pronounced immunomodulatory activity, migration, and re-growth of SH-SY5Y cells in the scratch model. Furthermore, priming of MSC with pro-inflammatory cytokine (IFN-γ) resulted in different proteomic profiles of conditioned media from both sources, which had the highest effect on SH-SY5Y proliferation and neurite outgrowth in terms of the length of neurites (pAT-MSCCM) compared to the control group (DMEM). Altogether, our results highlight the potential of primed and non-primed MSCCM as a therapeutic tool for neurodegenerative diseases, although some differences must be considered.